2021
DOI: 10.1111/bph.15515
|View full text |Cite
|
Sign up to set email alerts
|

Blocking glutamate mGlu5 receptors with the negative allosteric modulator CTEP improves disease course in SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: Background and PurposeThe pathogenesis of amyotrophic lateral sclerosis (ALS) is not fully clarified, although excessive glutamate (Glu) transmission and the downstream cytotoxic cascades are major mechanisms for motor neuron death. One and 5 metabotropic Glu (mGlu1,5) receptors are over-expressed in ALS and regulate cellular disease processes. We reported that mGlu5 receptor expression and function are already altered at early symptomatic stages in the SOD1 G93A mouse model of ALS and that knocking-down mGlu5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 84 publications
1
31
0
Order By: Relevance
“…Based on the above evidence, as the subsequent translational application of the data reported in this paper, our research groups are currently involved in carrying out studies aimed at testing the efficacy of MSC-derived EVs intranasally administered in SOD1 G93A ALS mice by performing a comprehensive panel of in vivo functional studies, as well as ex vivo histological and molecular analyses, as previously reported [ 89 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 98%
“…Based on the above evidence, as the subsequent translational application of the data reported in this paper, our research groups are currently involved in carrying out studies aimed at testing the efficacy of MSC-derived EVs intranasally administered in SOD1 G93A ALS mice by performing a comprehensive panel of in vivo functional studies, as well as ex vivo histological and molecular analyses, as previously reported [ 89 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, the total genetic ablation of mGluR1 receptor in the SOD1 G93A mouse model produced a very serious ataxic and detrimental phenotype (unpublished results), thus excluding possible therapeutic approaches using mGluR1 pharmacological antagonists. Then, we tested the effect of the chronic oral administration of the mGluR5 NAM CTEP [ 311 ]. Differing from the mGluR5 genetic ablation, the pharmacological treatment was started after symptom onset and maintained until the late symptomatic stage of the disease [ 311 ].…”
Section: Microglia and Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Perhaps confusingly, the same group treated SOD1 G93A mice with the mGlu 5 NAM CTEP and found that low doses improved motor skills and prolonged survival in female mice only. With an increased CTEP dose, improvements were seen in both sexes, but with improvements in the female mice being more pronounced ( Milanese et al, 2021 ). Why genetic blockade of mGlu 5 and blockade with a NAM showed differences in sex-specific responses requires further thought.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…As with astrogliosis, the genetic or pharmacological blockade of mGlu 5 in AD and ALS rodent models led to a reduction in microgliosis ( Bonifacino et al, 2017 ; Abd-Elrahman K. S. et al, 2020 ; Milanese et al, 2021 ). As reactive microglia have a neurotoxic effect mediated by the secretion of proinflammatory cytokines and chemokines and the release of excitotoxic levels of glutamate ( Barger and Basile, 2001 ; Hemonnot et al, 2019 ), it could be assumed that reducing their levels would be neuroprotective.…”
Section: Neuroinflammationmentioning
confidence: 99%